Menerapkan Algoritma Hill Cipher dan Matriks 2x2 Dalam Mengamankan File Teks Menggunakan Kode ASCII - Nurharianna Siregar; Ilham Faisal; Divi Handoko (LKP Unity Academy, 2022)
In today's technological developments, information (messages) is a basic need for society. Therefore the security of an information is very important. To secure the information required a technique that can secure the data, namely cryptography. Therefore, the author makes an application that can keep confidential information. In this application, the author uses a cryptographic method, namely the hill cipher method, where the hill cipher has two processes in encoding messages, namely encryption and description. In this encryption and description process, a matrix key is used. The matrix key used by the author is a 2x2 matrix. Making this application using the Python programming language. The result to be achieved from this research is the creation of an application that can encode confidential information (messages).